Ø±ÙˆØ§ÙŠØ© ØÙØµØ© Ø¨Ù†Øª Ø³ÙŠØ±ÙŠÙ†: Ø¯Ø±Ø§Ø³Ø© Ø¹Ù„Ù‰ Ø¬ÙˆØ§Ù†Ø¨ Ù…ÙˆØ¶ÙˆØ¹ Ø§Ù„ØØ¯ÙŠØ« - Lukman, Jannah (Al-Bukhari : Jurnal Ilmu Hadis, 2022)
Among those who contributed a major role in the transmission off the Hadith of the Prophet Muhammad Peace Be Upon Him were the female tabi‘in. This study wants to explain what aspects of narration are contained in the history of Hafshah binti Sirin as a tabi‘in women who who are known as one of Islamic Law Scholars. The method used is the library research method, which collects all the narrations from her and then categorizes the subject according to the aspect of the theme of the hadith. The approach used is the hadith theme approach which departs from the fiqh al-Hadith. Thus, there are 36 Hadiths which are divided into 5 aspects of narration, namely aspect of faith as many as 2 Hadith; aspect of law as many as 14 Hadith; aspect of ethic as many as 8 Hadith; aspect of virtues of deeds as many as 10 Hadith; and aspect of companions and tabi‘in's athar as many as 2 Hadith. In addition, based on takhrij and the description of the sanad tree, it was found that there were many marfu Hadiths. Meanwhile, there are also some hadith mauquf and maqthu.